Slang As A Cross-Generational Language and Its Influence On Indonesian Language In The Digital Era: A Morphological Study - Abbas, Asriani; Abbas, Abbas; Rasyid, Kaharuddin; Rabiah, Sitti (Journal of Ecohumanism, 2025)
This study aims to explain the structure of word characters in slang language that is widely used by generation Z and its influence on the use of Indonesian. The approach used is qualitative in this research. Data collection was carried out through observation and recording of the use of slang on social media such as Twitter, Facebook, Instagram, WhatsApp, and Tiktok as well as daily communication by students of the Faculty of Cultural Sciences at Hasanuddin University. Data collection was carried out purposively, namely the speech of students who are included in generation Z (aged 19 - 24 years). After the data was collected, data identification and text analysis were carried out using morphological theory, especially the process of word formation through abbreviation. The results of the study show that the use of slang on social media is related to standard language in terms of morphology, especially abbreviation. The process of creating slang by generation Z Indonesia generally experiences abbreviation (shortening of words). Four types of abbreviations were found in slang language, namely: (1) brevity, (2) acronym, (3) hyphenation, and (4) contraction. Although slang contains abbreviations from local and foreign languages, its use has its own rules that follow the general structure of Indonesian. The positive and negative influences of slang on the use of Indonesian are also revealed. It cannot disrupt the core axis of Indonesian because slang is considered a form of variation or style of language used by generation Z in interacting on social media.